Theories of trans/languaging and trans-semiotizing: implications for content-based education classrooms - Lin, Angel M. Y. (International journal of bilingual education and bilingualism, 2019)
Translanguaging theories emphasize a fluid, dynamic view of language and differ from code-switching/mixing theories by de-centring the analytic focus from the language(s) being used in the interaction to the speakers who are making meaning and constructing original and complex discursive practices. Trans-semiotizing theories further broaden the focus to analyse language as entangled with many other semiotics (e.g. visuals, gestures, bodily movement) in meaning making. In this paper recent developments in trans/languaging and trans-semiotizing theories are discussed in conjunction with fine-grained classroom analyses to illustrate the key role played by trans/languaging and trans-semiotizing practices in the dialogic construal of content meaning in content-based education.